2009
DOI: 10.1071/wr09047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prefeeding on foraging patterns of brushtail possums (Trichosurus vulpecula) about prefeed transects

Abstract: Context. Brushtail possums (Trichosurus vulpecula) are a major pest of native biodiversity and agricultural production in New Zealand. To maximise the effectiveness of control operations, prefeeding (free-feeding) of non-toxic bait before poison is often used, but the mechanisms by which it does so, remain unclear. One possibility is that prefeeding changes foraging patterns and space use in ways that increase the likelihood of possums finding and eating a lethal dose of poison bait.Aim. To determine whether p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The lesser reductions in rat and possum activity in the blocks that did not receive prefeed are consistent with previous research showing that the use of prefeed increases kill rates 14, 22. However, the results did not support the hypothesis that clustering of bait might obviate the need for using prefeed by ensuring most first‐time encounters by pests with toxic bait were with a lethal dose of 1080.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The lesser reductions in rat and possum activity in the blocks that did not receive prefeed are consistent with previous research showing that the use of prefeed increases kill rates 14, 22. However, the results did not support the hypothesis that clustering of bait might obviate the need for using prefeed by ensuring most first‐time encounters by pests with toxic bait were with a lethal dose of 1080.…”
Section: Discussionsupporting
confidence: 69%
“…This is likely to be true for rats, as their smaller body size means that even small bait fragments are likely to be lethal (obviating the need for multiple bait encounters and the consequent need for overbaiting). For possums, however, it is likely that use of prefeed may also improve efficacy by causing animals to range more widely than usual, and that this helped them find toxic bait clusters more quickly 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the bird monitoring programme was to collect mortality and productivity data associated with 1080 operations for some species not previously monitored and to collect mortality and productivity data for species that had not been monitored during 1080 operations for more than 5 years: there have recently been substantial changes in 1080 sowing rates (Veltman & Pinder ; Veltman & Westbrooke ) and the use of prefeed (Warburton et al . ).…”
Section: Preliminary Outcomes Of the Aerial Controlmentioning
confidence: 97%
“…Mortality of some bird species during 1080 operations is known to occur (Veltman & Westbrooke 2011; Morris et al 2016), but more importantly, productivity increases after 1080 operations (Powlesland et al 1999(Powlesland et al , 2000(Powlesland et al , 2003. The aim of the bird monitoring programme was to collect mortality and productivity data associated with 1080 operations for some species not previously monitored and to collect mortality and productivity data for species that had not been monitored during 1080 operations for more than 5 years: there have recently been substantial changes in 1080 sowing rates (Veltman & Pinder 2001;Veltman & Westbrooke 2011) and the use of prefeed (Warburton et al 2009). Preliminary data analysis from six of the nine bird and bat species monitored during Battle for our Birds showed that some Kea (Nestor notabilis) were killed by 1080, and some Rock Wrens (Xenicus gilviventris) disappeared soon after the application of 1080 (although the cause of the latter is uncertain).…”
Section: Birdsmentioning
confidence: 99%